Maxillomandibular Advancement with the Use of Virtual Surgical Planning and the CAD/CAM Technology in OSA Surgery: Volumetric Analysis of the Posterior Airway Space - Eleonora Segna; Funda Goker; Giulia Tirelli; Massimo Del Fabbro; Aldo Bruno Giannì; Giada Anna Beltramini; Diego Sergio Rossi (Medicina)
Background and Objectives: Obstructive sleep apnea is an extremely diffuse pathology that, if left untreated, can lead to very serious cardiovascular consequences. The primary goal of treatment is to maintain airflow in the upper airway tract, which can be obtained thanks to orthognathic surgery such as maxillo-mandibular advancement (MMA). This procedure increases the volume of the posterior airway space (PAS)—a parameter considered fundamental in OSA physiology. However, the correlation between the degree of advancement, the volume increase, and the clinical improvement in OSA is not yet clear, even in patients who undergo virtual surgical planning. Aiming to test the correlation of these parameters and the role of PAS volume changes, we present our pre- and post-operative volumetric analysis of the PAS using cone beam computed tomography (CBCT) following CAD/CAM-assisted maxillomandibular advancement. Materials and Methods: We collected information from patients who underwent MMA for moderate or severe OSA, planned virtually with custom-made devices, between 2020 and 2022 at the Maxillofacial Surgery and Odontostomatology Unit of the Policlinico Hospital in Milan. The degree of mandibular advancement (pogonion antero-posterior advancement) was noted. All patients underwent pre- and post-operative CBCT and pre- and post-operative polysomnography to measure the Apnea–Hypopnea Index (AHI) parameters. Both exams were performed within six months before and after surgery. The surgeries were planned virtually along with the production of custom-made devices (cutting guides and mandibular osteosynthesis plates). Volumetric analysis of the PAS was performed pre- and post-CBCT images using medical segmentation software (Mimics, Materialise, Mimcs 26.0). Results: Ten patients (nine men and one woman) with a mean age of 51 years were included in this study. The mean pogonion advancement was 14.5 mm, ranging from 13.8 to 15.6. The mean pre-surgical AHI was 52.31 events/h, while the mean post-surgical AHI was 5.94 events/h (SD 5.34). The improvement in AHI was statistically significant (Wilcoxon matched-pairs signed-rank test, p value 0.004). The mean pre-surgical PAS volume was 8933 mm3, while the mean post-surgical volume was 10,609 mm3. In 8 out of 10 patients, the volume increased, with a mean increase of 2640 mm3 (max. 5183, min. 951), corresponding to a percentage increase variation ranging from 78% to 6%. In two patients, the volume decreased by 1591 (−16%) and 2767 mm3 (−31%), respectively. The difference between pre- and post-operative results was not statistically significant (paired t-test, p value 0.033). Conclusions: The results obtained confirm the efficacy of virtually planned MMA performed with custom-made devices in OSA therapy. However, they also show that PAS volume should not be used as a comprehensive parameter for OSA treatment evaluation because it does not always have a positive correlation with advancement and AHI.